2021
DOI: 10.3390/ijms22147475
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Tau Protein

Abstract: Neurofibrillary tangles, which consist of highly phosphorylated tau protein, and senile plaques (SPs) are pathological hallmarks of Alzheimer’s disease (AD). In swollen axons, many autophagic vacuoles are observed around SP in the AD brain. This suggests that autophagy function is disturbed in AD. We used a neuronal cellular model of tauopathy (M1C cells), which harbors wild type tau (4R0N), to assess the effects of the lysosomotrophic agent NH4Cl, and autophagy inhibitors chloroquine and 3 methyladenine (3MA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 88 publications
(154 reference statements)
0
35
0
Order By: Relevance
“…Previous studies demonstrated that soluble tau is cleared by endosomal microautophagy and chaperon-mediated autophagy, while intracellular insoluble tau is degraded by macroautophagy [ 21 24 ]. However, hyperphosphorylated tau still accumulates in PS1 F105C neurons, revealing that autophagy system is insensitive to tau accumulation in PS1 F105C neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that soluble tau is cleared by endosomal microautophagy and chaperon-mediated autophagy, while intracellular insoluble tau is degraded by macroautophagy [ 21 24 ]. However, hyperphosphorylated tau still accumulates in PS1 F105C neurons, revealing that autophagy system is insensitive to tau accumulation in PS1 F105C neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The clearance of physiological and pathological tau is mainly mediated by the ubiquitin proteasome system and autophagy/lysosomal degradation pathway. In AD patients, the neuronal lysosome system was dysregulated ( Sundelof et al, 2010 ; Wang X. M. et al, 2021 ; Liu et al, 2021 ; Hamano et al, 2021 ). The results of this study show that CR promotes the degradation of pathological tau mainly through the lysosome system rather than the proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…It suppresses inflammation and promotes vasorelaxation in rheumatoid arthritis and hypertension, respectively ( Su et al, 2020 ; Behl et al, 2021 ; Mokgalaboni et al, 2021 ). So far, several action mechanisms for curcumin in biological aging have been proposed, including mitophagy/autophagy induction, inflammation and oxidation suppression, AMPK and SIRT1 pathway stimulation, senescence, mTOR inhibition, and mitochondrial function maintenance ( Hamano et al, 2021 ; Zia et al, 2021 ; Dhapola et al, 2022 ). This broad range of effects of curcumin indicates that curcumin or its semi-synthetic derivatives target or bind to numerous intracellular macromolecules or modulate transcriptional responses to influence diverse aging-related pathways.…”
Section: Clinical Utility and Control Of Biological Aging And Age-rel...mentioning
confidence: 99%